UNIMUDA Sorong Students' Perceptions of Permenristekdikti No. 33 Of 2018 Concerning Name of Study Programs in Higher Education - Jumroh, Siti Fatihaturrahmah Al (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Since this Ministerial Regulation comes into force, namely Permenristekdikti No 33 of 2018 concerning naming study programs at universities, the Minister of Research, Technology and Higher Education Regulation Number 15 of 2017 concerning Naming Study Programs in Higher Education (State Gazette of the Republic of Indonesia of 2017 Number 124), is revoked, and declared invalid. This study aims to reveal how the UNIMUDA Sorong Student Perceptions of the Minister of Research, Technology and Higher Education No. 33 of 2018 concerning the Naming of Study Programs in Higher Education. The approach used in this research is qualitative with descriptive method. The indicator used to measure this is Permenristekdikti No 33 of 2018 itself starting from article 1 to article 8. The respondents used are students of UNIMUDA Sorong who are in the Faculty of Teacher Training and Education (FKIP). The research data was obtained through the distribution of a questionnaire totaling 5 questions guided by the research indicators, namely Permenristekdikti No 33 of 2018 concerning the naming of study programs at universities. Furthermore, the data collected was then analyzed using descriptive data analysis according to Miles and Huberman. The results of the analysis show that the perception of Unimuda Sorong students towards Permenristekdikti No. 33 of 2018 is quite good with the number of students' understanding and perception of 94%.